Radiation Emission and Absorption by Astrophysical Jets from XRBs - Papavasileiou, Theodora; Kosmas, Odysseas; Sinatkas, Ioannis (HNPS Advances in Nuclear Physics, 2023)
High-energy particles and radiation such as protons, pions, muons, neutrinos and gamma-ray photons are known to emit from collimated outflows of magnetized astrophysical plasma known as jets. They are being ejected by Active Galactic Nuclei or X-ray binary systems consisting of a companion star accreting mass onto a black hole or a neutron star. Our work focuses on the calculation of the produced particle energy distributions and mainly on the intensity of gamma-rays. We apply this model to prominent examples of Black Hole XRBs such as Cygnus X-1, SS 433, GRS 1915+105, etc. We also study and work on calculating the absorption of emitted gamma-rays by soft and hard X-ray radiation fields originating from the system’s accretion disc, corona and companion star that could strongly affect the jet’s gamma-ray intensity that finally reaches the Earth.